Optimization of Ship Stability through Response Surface Methodology: Enhancing Safety and Performance via Cross Curve Analysis - Kukuh Izatullah; Muhammad Arif Budiyanto; Wanda Rulita Sari (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Optimizing the cross curves of ship stability through the application of Response Surface Methodology (RSM) requires a complex interplay between factors such as hull shape, beam, and draft significantly influences a ship's stability, which is crucial for the safety of the crew, passengers, and cargo. By employing RSM, this research systematically examines these factors, developing a second-order polynomial model to describe their relationship with stability metrics. The experiments were conducted using Design-Expert 13® software, which facilitated the design of experiments, data collection, model development, and validation. The optimized model revealed that while the overall impact of individual factors might not be significant, their combined interactions provide a robust predictive capability for ship stability. The results demonstrated that the optimized input variables led to improved stability outcomes, minimizing moment trim while maximizing longitudinal and transverse metacentric heights, thereby ensuring better performance and safety across various sea conditions.